Subspecies differentiation in an enigmatic chaparral shrub species. Issue 6 (4th June 2020) - Huang, Yi; Morrison, Glen R.; Brelsford, Alan; Franklin, Janet; Jolles, Diana D.; Keeley, Jon E.; Parker, V. Thomas; Saavedra, Natalie; Sanders, Andrew C.; Stoughton, Thomas R.; Wahlert, Gregory A.; Litt, Amy
Abstract : Premise: Delimiting biodiversity units is difficult in organisms in which differentiation is obscured by hybridization, plasticity, and other factors that blur phenotypic boundaries. Such work is more complicated when the focal units are subspecies, the definition of which has not been broadly explored in the era of modern genetic methods. Eastwood manzanita ( Arctostaphylos glandulosa Eastw.) is a widely distributed and morphologically complex chaparral shrub species with much subspecific variation, which has proven challenging to categorize. Currently 10 subspecies are recognized, however, many of them are not geographically segregated, and morphological intermediates are common. Subspecies delimitation is of particular importance in this species because two of the subspecies are rare. The goal of this study was to apply an evolutionary definition of "subspecies" to characterize structure within Eastwood manzanita. Methods: We used publicly available geospatial environmental data and reduced‐representation genome sequencing to characterize environmental and genetic differentiation among subspecies. In addition, we tested whether subspecies could be differentiated by environmentally associated genetic variation. Results: Our analyses do not show genetic differentiation among subspecies of Eastwood manzanita, with the exception of one of the two rare subspecies. In addition, our environmental analyses did not show ecological differentiation, though limitations of the analysis prevent strong conclusions. Conclusions: Genetic structure within Eastwood manzanita does not correspond to current subspecies circumscriptions, but rather reflects geographic distribution. Our study suggests that subspecies concepts need to be reconsidered in long‐lived plant species, especially in the age of next‐generation sequencing.